APLIKASI PUPUK BOKASHI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELEDRI (Apium graveolens) - I Gusti Ayu Diah Yuniti; Martinus Irlan; Cokorda Javandira; I Made Sukerta (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2025)
Celery (Apium graveolens) is a high-value vegetable crop in Indonesia, favored by many consumers. However, its production remains relatively low due to suboptimal cultivation techniques. One contributing factor is the lack of appropriate fertilization practices, which directly affect plant growth and yield. This study aimed to (1) evaluate the effect of bokashi fertilizer on the growth of celery plants and (2) determine the optimal dose of bokashi fertilizer for enhancing celery growth and yield. A Completely Randomized Design (CRD) was used with six treatment levels: no fertilizer (P0), bokashi at 5 tons/ha (P1), 10 tons/ha (P2), 15 tons/ha (P3), 20 tons/ha (P4), and 25 tons/ha (P5), each replicated four times for a total of 24 experimental units. The results indicated that bokashi fertilizer significantly influenced all measured growth parameters, including plant height (cm), number of leaves, root length (cm), total fresh weight (g), and oven-dry weight (g). Among the treatments, the application of 75 g of bokashi per 10 kg of soil produced the best results across all observed variables. These findings suggest that the appropriate use of bokashi fertilizer can substantially improve the growth and productivity of celery plants in Indonesia.